Moldova : Assessment of the Public Procurement System - World Bank Group (World Bank, Washington, DC, 2021)
The main development objective of the work has been to use the MAPS assessment tool to assess the quality and effectiveness of Moldova’s public procurement system and on that basis create an evidence base for future reforms. In order to achieve this objective, the assessment has endeavored to: identify strengths and weaknesses of the public procurement system in Moldova, and benchmarking it with international best practices and standards; identify any substantial gaps that negatively impact the quality and performance of the public procurement system; help the Government to prioritize efforts in public procurement reform to enable: balanced accountability mechanisms between the Government, citizens, and the private sector; governance of risk management in the procurement cycle; and integration of the public procurement system with the overall public finance management, budgeting and service delivery processes; provide a comparative analysis of the country’s two parallel procurement systems (Government and State Owned Enterprises (SOEs)), between each other and against MAPS standards; and suggest recommendations to enhance the public procurement system and jointly with the Government elaborate an action plan for reforms to continuously enhance the quality and performance of the procurement system; In addition, and at the request of the Ministry of Finance, the assessment will include spend analysis which will help the Government reduce procurement costs and improve efficiency in public procurement to generate savings.